2023
DOI: 10.3390/cancers15153760
|View full text |Cite
|
Sign up to set email alerts
|

Textbook Oncological Outcomes for Robotic Colorectal Cancer Resections: An Observational Study of Five Robotic Colorectal Units

Abstract: Background: The quality of care of patients receiving colorectal resections has conventionally relied on individual metrics. When discussing with patients what these outcomes mean, they often find them confusing or overwhelming. Textbook oncological outcome (TOO) is a composite measure that summarises all the ‘desirable’ or ‘ideal’ postoperative clinical and oncological outcomes from both a patient’s and doctor’s point of view. This study aims to evaluate the incidence of TOO in patients receiving robotic colo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(6 citation statements)
references
References 22 publications
0
6
0
Order By: Relevance
“…The main characteristics of the included studies are shown in Table 1[6,[8][9][10][11][12][13][14][15][16][17][18][19][20][21][22][23]. Twelve studies (70.6%) have been published in the last 3 years and 94.1% in the last 5 years.…”
Section: Resultsmentioning
confidence: 99%
“…The main characteristics of the included studies are shown in Table 1[6,[8][9][10][11][12][13][14][15][16][17][18][19][20][21][22][23]. Twelve studies (70.6%) have been published in the last 3 years and 94.1% in the last 5 years.…”
Section: Resultsmentioning
confidence: 99%
“…To further evaluate surgical quality and surgical safety between the two groups, we utilized a comprehensive index called TO, which assesses surgical outcomes from multiple dimensions as a single desirable measure 38 . This widely used index has been extensively applied in abdominal surgery 39 41 . Recent studies have shown that achieving TO is associated with improved long-term prognosis in HCC patients undergoing hepatectomy 42 , 43 .…”
Section: Discussionmentioning
confidence: 99%
“…This diversity in parameter selection highlights the ongoing efforts within the medical community to refine the concept of textbook outcomes. Additionally, Azevedo et al’s recent research on robotic colorectal cancer resections formulated TO, based on no conversions to open and no complications with a Clavien–Dindo score of ≥3, LOS of ≤14, radical resection, no 30-day readmission, and no 30-day mortality [ 13 ]. The decision to include only complications with a CD score of ≥3 contrasts with the approach taken in the majority of publications and our data, where all complications were considered in the assessment of TO.…”
Section: Discussionmentioning
confidence: 99%
“…The decision to include only complications with a CD score of ≥3 contrasts with the approach taken in the majority of publications and our data, where all complications were considered in the assessment of TO. Consequently, the percentage of successfully achieved TO is notably higher, observed in 77.4% of the patients [ 13 ]. Certain authors emphasize the lack of a stoma post-surgery to be a crucial component of TO [ 14 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation